2009
DOI: 10.1890/08-1805.1
|View full text |Cite
|
Sign up to set email alerts
|

Does hunting regulate cougar populations? A test of the compensatory mortality hypothesis

Abstract: Abstract. Many wildlife species are managed based on the compensatory mortality hypothesis, which predicts that harvest mortality (especially adult male mortality) will trigger density-dependent responses in reproduction, survival, and population growth caused via reduced competition for resources. We tested the compensatory mortality hypothesis on two cougar (Puma concolor) populations in Washington, USA (one heavily hunted and one lightly hunted). We estimated population growth, density, survival, and reprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
183
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(200 citation statements)
references
References 34 publications
13
183
2
1
Order By: Relevance
“…We could not reject the null hypothesis of additivity in the Monroe population once parameter uncertainty was accounted for, a finding that has been supported by other carnivore studies (Cooley et al, 2009;Creel and Rotella, 2010;Robinson et al, 2014). Indeed, Cooley et al (2009) observed that although immigration compensated for hunting mortalities, they found like us that compensation via other vital rates (e.g.…”
Section: Figmentioning
confidence: 42%
See 1 more Smart Citation
“…We could not reject the null hypothesis of additivity in the Monroe population once parameter uncertainty was accounted for, a finding that has been supported by other carnivore studies (Cooley et al, 2009;Creel and Rotella, 2010;Robinson et al, 2014). Indeed, Cooley et al (2009) observed that although immigration compensated for hunting mortalities, they found like us that compensation via other vital rates (e.g.…”
Section: Figmentioning
confidence: 42%
“…the same question by assessing the human-carnivore interaction as a predator-prey relationship (Cooley et al, 2009;Creel and Rotella, 2010;Sparkman et al, 2011;Robinson et al, 2014); yet, only one of these studies has addressed the problem of sampling variance in competing mortality risks (Murray et al, 2010). By adopting a similar approach to that of Murray et al (2010) in cougars, a carnivore with a completely different social structure (i.e.…”
Section: Figmentioning
confidence: 99%
“…Specifi cally, a review of multiple studies showed that removal of breeding wolves, Canis lupus, led to decreased wolf packs or to the dissolution of packs, and that pup survival was higher in larger packs and was correlated with the presence of auxiliary nonbreeders (Brainerd et al, 2008). Heavy hunting pressure on cougar populations, Puma concolor, was correlated with increased immigration, reduced kitten survival, and reduced female population growth (Cooley et al, 2009).…”
Section: Extinction Risk and Potential For Recoverymentioning
confidence: 99%
“…Trophy hunting uses a quota system approach that promotes sustainable off-takes by removing a fraction of natural population growth rates, which arguably falls within the compensatory mortality range and has a negligible impact on overall ecology of wildlife species [13,14]. The quota system used in trophy hunting is based on ecological theory, that is, maximum sustainable yield (MSY), set 2 International Journal of Biodiversity in such a way that off-take levels are always below the growth rate of the target species at any given time [11,15,16].…”
Section: Introductionmentioning
confidence: 99%